আমার বেলা যে যায় - মুসা, এবিএম (ঢাকা : প্রথমা প্রকাশন, 2014)
Autobiographical reminiscences of E.Bi.Ema. Mūsā, journalist from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Musa, ABM; Journalists -- Bangladesh -- Biography